Mengapa Bahasa Arab Sulit Dipahami? Perspektif Langsung dari Guru dan Siswa - Muhammad Sholikhul Fikri Arafat; Mohammad Nu'man (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
This study examines the factors that contribute to students’ difficulties in learning Arabic at the Madrasah Tsanawiyah level, with a particular focus on psychological aspects and pedagogical approaches implemented by teachers. The research employed a descriptive qualitative method through direct classroom observation and the distribution of open-ended questionnaires to both students and teachers. The findings reveal that students frequently struggle with comprehending linguistic structures such as nahwu and sharaf, as well as with memorizing and applying vocabulary (mufrodat). Psychologically, students exhibit anxiety, fear of making mistakes, and a lack of self-confidence when asked to speak in Arabic. Additionally, teaching practices tend to remain teacher-centered, relying on lecture-based instruction and rote memorization, which fail to actively engage students in the learning process. The limited use of interactive learning media and the lack of communicative Arabic practice further reinforce students’ negative perception of Arabic learning. This study recommends the implementation of more communicative, creative, and student-centered pedagogical approaches that take into account students’ emotional conditions and individual learning needs. In doing so, Arabic language learning can become more enjoyable, applicable, and effective in enhancing students’ linguistic competence and learning motivation. Keywords: Perspective, Psychology, Pedagogy, Motivation, Vocabulary